Analisis Problematika Pembelajaran Bangun Ruang dan Alternatif Strategi Pemecahannya dalam Pelajaran Matematika di Sekolah Dasar - Hilmawan, Adiyatma Zaki Nabil; Fauzi, Aditya Zaki Gemawan; Hartini, Kristina Aspri; Indrapangastuti, Dewi; Wahyudi, Achmad Basari Eko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Understanding the foundational concepts and dimensions of geometric solids represents a critical component of mathematical competency at the elementary education level. However, numerous studies have consistently reported that students continue to experience significant challenges in grasping the properties and structures of three-dimensional figures. This article aims to investigate the recurring obstacles encountered in teaching spatial geometry at the elementary school level and to explore evidence-based pedagogical strategies to address them, drawing upon findings from prior scholarly research. The method used is a systematic literature study of scientific articles published between 2016 and 2025, with inclusion criteria being articles discussing difficulties in learning mathematics in elementary schools, particularly on the topic of geometric shapes, and published in nationally or internationally accredited journals. Exclusion criteria include articles that are not relevant to the focus of geometric shapes, not based on empirical research, or not available in full text. Articles were searched using the keywords: "learning difficulties", "elementary school mathematics", and "geometric shapes". The results of the study indicate that students' difficulties in learning geometric shapes are closely related to a weak understanding of basic concepts, misconceptions about mathematical terms, low learning motivation, and the lack of optimization of the use of learning media. Several recommended strategies to overcome these problems include: (1) the use of interesting and concrete learning media; (2) strengthening basic concepts before students are introduced to more complex concepts; (3) the application of active and enjoyable learning methods; (4) increasing students' active involvement in the learning process; and (5) the use of visual, narrative, and exploratory educational media, such as Pop-Up Books and math comics. This study is expected to be the basis for designing a more effective and enjoyable learning activity approach to introduce the concept of spatial shapes to students at elementary school level.Penguasaan terhadap konsep dan ukuran bangun ruang termasuk kompetensi dasar esensial pada kegiatan belajar matematika di jenjang sekolah dasar. Berbagai temuan penelitian menunjukkan bahwa siswa masih mengalami hambatan yang cukup signifikan dalam memahami materi ini. Studi ini dirancang untuk melakukan identifikasi serta analisis mendalam terhadap permasalahan yang timbul dalam pembelajaran bangun ruang di tingkat sekolah dasar, serta mengeksplorasi strategi alternatif yang dapat diterapkan untuk mengatasinya berdasarkan temuan-temuan studi sebelumnya. Metode yang digunakan adalah studi literatur sistematis terhadap artikel-artikel ilmiah yang dipublikasikan dalam kurun waktu 2016 hingga 2025, dengan kriteria inklusi berupa artikel yang membahas kesulitan pembelajaran matematika di sekolah dasar, khususnya pada topik bangun ruang, dan dipublikasikan dalam jurnal terakreditasi nasional atau internasional. Kriteria eksklusi mencakup artikel yang tidak relevan dengan fokus bangun ruang, tidak berbasis penelitian empiris, atau tidak tersedia dalam teks lengkap. Artikel ditelusuri menggunakan kata kunci: “kesulitan pembelajaran”, “matematika sekolah dasar”, dan “bangun ruang”.  Hasil kajian menunjukkan bahwa kesulitan siswa dalam mempelajari bangun ruang berkaitan erat dengan lemahnya pemahaman terhadap konsep dasar, miskonsepsi terhadap istilah matematika, rendahnya motivasi belajar, serta kurangnya optimalisasi penggunaan media pembelajaran. Beberapa strategi yang direkomendasikan untuk mengatasi permasalahan tersebut antara lain: (1) pemanfaatan media pembelajaran yang menarik dan bersifat konkret; (2) penguatan konsep dasar sebelum siswa dikenalkan pada konsep yang lebih kompleks; (3) penerapan metode pembelajaran yang aktif dan menyenangkan; (4) peningkatan keterlibatan aktif siswa dalam proses pembelajaran; serta (5) penggunaan media edukatif berbasis visual, naratif, dan eksploratif, seperti Pop-Up B,ok dan komik matematika. Kajian ini diharapkan menjadi landasan dalam merancang pendekatan kegiatan belajar yang lebih efektif dan menyenangkan guna memperkenalkan konsep bangun ruang kepada siswa di jenjang sekolah dasar.